VD_FINDINFO Jug / 2012 / 296 vom 6. Juni 2012 - VD Tribunal cantonal (2012)
LÉSION CORPORELLE SIMPLE, VOIES DE FAIT, EXCÈS, LÉGITIME DÉFENSE, ÉTAT DE NÉCESSITÉ, FAUTE DU TIERS | 44 al. 1 CO, 123 ch. 1 al. 1 CP, 126 al. 1 CP, 15 CP, 16 CP, 17 CP, 433 al. 1 CPP(CH), 433 al. 2 CPP (CH)